Views and impressions of the French doctor Desfontaines on central and western Algeria in 1785 translation and commentary - belamri, fateh (Journal of Social Sciences and Humanities, 2023)
These pages deal with the observations and impressions of a French doctor, a botanist named R.L.Desfontaines, about the Algerian center and west in 1785, when he visited it as part of a scientific expedition by Louis XVI (XVI) to collect samples of rare plants and animals in the region for the benefit of Royal palace. It was dominated by the scientific and geographical nature, and was interspersed with some .opinions on the political, social, economic and cultural aspects. In it the reader finds the characteristics of this region in the mid-eighteenth century of the 18th century, especially in the topographical aspect, topography, vegetation cover and the water network, with a precise descriptive perspective, because its writer was an eyewitness to much of what he wrote down, even though he misspelled the names of places, cities and villages. However, he turned out to be a skilled recorder of what was written down and an accurate observer of what was described. In this sense, who is Rainier Louis Desfontein? What are his observations and impressions of the Algerian center and west during the period he visited? Are his news and knowledge that he presents true or tainted by falsity and falsity? To what extent did his scientific mission succeed through this visit?